p38 mediated ACSL4 phosphorylation drives stress-induced esophageal squamous cell carcinoma growth through Src myristoylation - Qiang Yuan; Yunshu Shi; Junyong Wang; Yifei Xie; Xiaoyu Li; Jimin Zhao; Yanan Jiang; Yan Qiao; Yaping Guo; Chengjuan Zhang; Jing Lu; Tongjin Zhao; et al. (Nature Communications)
Abstract The comprehension of intricate molecular mechanisms underlying how external stimuli promote malignancy is conducive to cancer early prevention. Esophageal squamous cell carcinoma (ESCC) is considered as an external stimuli (hot foods, tobacco, chemo-compounds) induced cancer, characterized by stepwise progression from hyperplasia, dysplasia, carcinoma in situ and invasive carcinoma. However, the underlying molecular mechanism governing the transition from normal epithelium to neoplastic processes in ESCC under persistent external stimuli has remained elusive. Herein, we show that a positive correlation between p38 and ERK1/2 activation during the progression of ESCC. We identify that phosphorylation of ACSL4 at T679 by p38 enhances its enzymatic activity, resulting in increased production of myristoyl-CoA (C14:0 CoA). This subsequently promotes Src myristoylation and activates downstream ERK signaling. Our results partially elucidate the role of ACSL4 in mediating stress-induced signaling pathways that activate growth cascades and contribute to tumorigenesis.